Evaluation of the level of cortisol, capillary blood glucose, and blood pressure in response to anxiety of patients rehabilitated with complete dentures - Goiato, Marcelo Coelho [UNESP]; Da Silva, Emily Vivianne Freitas [UNESP]; Cândido, Nádia Biage [UNESP]; Nóbrega, Adhara Smith [UNESP]; De Medeiros, Rodrigo Antonio; Sumida, Doris Hissako [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Dos Santos, Daniela Micheline [UNESP] (Springer Nature, 2019)
Background: The aim was to analyze the levels of stress of edentulous patients through the state-trait anxiety inventory (STAI) and salivary flow through the visual analogue scale (VAS) xerostomia questionnaire, as well as analyze the levels of cortisol, capillary blood glucose, and blood pressure (BP) before and after the installation of complete dentures. Methods: Fifty patients were evaluated. The STAI and VAS xerostomia questionnaire were applied before the installation of the prosthesis, on the day of its installation, and 1 month after the last recall visit. The BP measurement, as well as salivary and blood collections, were performed before the installation of the prothesis, and 1 month after the last recall visit. Data from the VAS xerostomia questionnaire and cortisol levels were submitted to ANOVA and the Tukey test (P =.05). Data from the STAI, as well as blood glucose and BP levels, were submitted to the Chi-square test (P =.05). The correlation between cortisol and blood glucose and between cortisol levels and BP was analyzed. Results: There was no statistically significant association between the questions of the VAS xerostomia questionnaire, STAI-state and STAI-trait scores, or the periods analyzed. However, the cortisol level collected in the morning decreased after the installation of the prosthesis. There was a correlation between cortisol and blood glucose and BP levels. Conclusions: The installation of complete dentures was beneficial for patients since it was probably responsible for the cortisol level reduction.
Keywords: Anxiety; Blood glucose; Blood pressure; Complete denture